Family income, parental education and brain structure in children and adolescents - Noble, Kimberly G; Houston, Suzanne M; Brito, Natalie H; Bartsch, Hauke; Kan, Eric; Kuperman, Joshua M; Akshoomoff, Natacha; Amaral, David G; Bloss, Cinnamon S; Libiger, Ondrej; Schork, Nicholas J; Murray, Sarah S; et al. (Nature neuroscience, 2015)
Socioeconomic status is associated with cognitive development, but the extent to which this reflects neuroanatomical differences is unclear. In 1,099 children and adolescents, family income was nonlinearly associated with brain surface area, and this association was greatest among disadvantaged children. Further, surface area mediated links between income and executive functioning. Socioeconomic disparities are associated with differences in cognitive development. The extent to which this translates to disparities in brain structure is unclear. We investigated relationships between socioeconomic factors and brain morphometry, independently of genetic ancestry, among a cohort of 1,099 typically developing individuals between 3 and 20 years of age. Income was logarithmically associated with brain surface area. Among children from lower income families, small differences in income were associated with relatively large differences in surface area, whereas, among children from higher income families, similar income increments were associated with smaller differences in surface area. These relationships were most prominent in regions supporting language, reading, executive functions and spatial skills; surface area mediated socioeconomic differences in certain neurocognitive abilities. These data imply that income relates most strongly to brain structure among the most disadvantaged children.